2012
DOI: 10.1007/s00262-012-1341-2
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin induces proliferation of NSCLC in vitro and in vivo: role of COX-2 and EGFR activation

Abstract: Lung cancer is frequently complicated by pulmonary infections which may impair prognosis of this disease. Therefore, we investigated the effect of bacterial lipopolysaccharides (LPS) on tumor proliferation in vitro in the non-small cell lung cancer (NSCLC) cell line A549, ex vivo in a tissue culture model using human NSCLC specimens and in vivo in the A549 adenocarcinoma mouse model. LPS induced a time- and dose-dependent increase in proliferation of A549 cells as quantified by MTS activity and cell counting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 50 publications
5
42
0
Order By: Relevance
“…Our findings suggest that LPS from E. coli 0111:B4 can promote A549 cell proliferation and induce oxidative stress and inflammation, which is consistent with previous studies (6,(31)(32)(33). Our data suggest that endotoxin is an applicable and powerful promoter of tumor cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings suggest that LPS from E. coli 0111:B4 can promote A549 cell proliferation and induce oxidative stress and inflammation, which is consistent with previous studies (6,(31)(32)(33). Our data suggest that endotoxin is an applicable and powerful promoter of tumor cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest that endotoxin is an applicable and powerful promoter of tumor cell proliferation. The escalation in metabolic activity was previously noted after 24 h of LPS treatment and A549 cells are well known to correspond to cellular proliferation (32). The obtained results indicate that beraprost treatment significantly reverse LPS-induced cell proliferation.…”
Section: Discussionsupporting
confidence: 72%
“…Celecoxib (CXB) is a cyclooxygenase 2-selective nonsteroidal anti-inflammatory drug (NSAID) that has been approved for the treatment of adult arthritis, and has been found to exhibit therapeutic effects on various types of cancers (19). Currently, CXB is widely being tested in clinical trials for its therapeutic activity against various cancers as a single agent and also in combination with other agents (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor volume was significantly greater than that of the A549 cells without LPS treatment and expression of the marker of proliferation, Ki-67, in tumor tissues was also significantly increased (18). Similarly, the in vivo data of the present study revealed that following grafting the MGC-803 gastric cancer cell line stimulated by LPS into the axilla of nude mice to establish tumor xenografts, there was an increase in tumor volume and weight in the LPS group, which was consistent with findings of a previous study (17).…”
Section: Discussionmentioning
confidence: 86%